Financial crisis interventions - Josef Schroth (Bank of Canada, 2016)
This paper develops a model of an economy where bank credit supports both productive investment and individual consumption smoothing in the face of idiosyncratic income risk. Bank credit is constrained by bank equity capital. When policy-makers inject equity capital during financial crises, they trade off stimulating credit supply immediately against long-term distortions related to funding equity injections. I calibrate my model and show that the bank equity capital injection that maximizes average utilitarian welfare redistributes from the poor to the wealthy. While wealthy savers benefit immediately from an increased supply of safe assets, less affluent borrowers and savers suffer from long-term distortions.
Keywords: E13; E32; E44; 330; Financial stability; Financial system regulation and policies; Lender of last resort; Credit and credit aggregates